Diameter : new generation AAA protocol : design, practice and applications /: new generation AAA protocol : design, practice and applications. (2015) - Tschofenig, Hannes; Decugis, Sebastien; Mahoney, Jean; Morand, Lionel; Korhonen, Jouni
No abstract available